Seeing beyond words: nanotechnology in hepatocellular carcinoma - a bibliometric study - Tuergan, Talaiti; Abulaiti, Aimitaji; Tulahong, Alimu; Zhang, Ruiqing; Yuan, Zhongdian; Lin, Yanze; Shao, Yingmei; Aji, Tuerganaili (Frontiers in Oncology, 2025)
BackgroundNanotechnology has increasingly been applied in the diagnosis and treatment of hepatocellular carcinoma (HCC) over the past two decades. This study aims to explore the utilization of nanotechnology in HCC through a bibliometric analysis, identifying key themes, trends, and contributions in this field.MethodsThe study utilized VOSviewer and CiteSpace software to perform a bibliometric analysis, evaluating scholarly contributions related to nanotechnology in HCC. The analysis focused on co-occurrence network relationships, publications, citations, and contributions from various entities and authors.ResultsThe analysis revealed a total of 2,968 articles, with China and the USA being the most prominent contributors in terms of publications and citations. Notable contributions were made by the Chinese Academy of Sciences and authors Gao Jie and Li Yan. LLOVET JM emerged as the most co-cited author, indicating a leadership role in the field. The “International Journal of Nanomedicine” was identified as the leading publisher, while “Biomaterials” ranked highest in citations. The research mainly focused on drug delivery systems and apoptosis, highlighting significant advancements in utilizing nanotechnology for HCC treatment.ConclusionThis bibliometric study underscores the critical role of nanotechnology in advancing the diagnosis and treatment of hepatocellular carcinoma, with a particular emphasis on drug delivery and apoptosis. The findings highlight the contributions of key countries, institutions, and authors, reflecting the global effort and collaboration in this rapidly evolving field.